Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS): discrete and regression-based norms for the Brazilian context - Spedo, Carina Tellaroli; Pereira, Danilo de Assis; Frndak, Seth Edward; Marques, Vanessa Daccach; Barreira, Amilton Antunes; Smerbeck, Alan; Silva, Pedro Henrique Rodrigues da; Benedict, Ralph H. B. (Arquivos de Neuro-Psiquiatria, 2022)
Background: The Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) has been recently developed as a brief, practical, and feasible tool for cognitive impairment in multiple sclerosis (MS). Objective: This study aimed to provide continuous and discrete normative values for the BICAMS in the Brazilian context. Methods: Normatization was achieved using six hundred and one healthy controls from the community assessed at five Brazilian geopolitical regions. Results: Mean raw scores, T scores, percentiles, and Z scores for each BICAMS measure are provided, stratified by age and educational level. Regression-based norms were provided by converting raw scores to scaled scores, which were regressed on age, gender, and education, yielding equations that can be used to calculate the predicted scores. Regression analyses revealed that age, gender, and education significantly influenced test results, as in previous studies. Conclusions: The normative data of the BICAMS to the Brazilian context presented good representativeness, improving its use in daily clinical practice.
Keywords: Multiple Sclerosis; Cognitive Dysfunction; Neuropsychology